SELF-SUFFICIENCY OPTIMIZATION OF STUDENTS LEARNING THROUGH MODULE - Atika Dwi Evitasari (Universitas Sebelas Maret, 2018)
Students are unique individual. Primary students are individuals who have stages develope concrete operasional. They have conditional of study what on help understanding learning material. According to obvious until will creating procces of study purpose for participants of students and will impact for reached competences will expect. Additionally, other things what needed interest are learning independent. Learning independent is a learn attitude what not depend to ones, include to teacher for continue. Existence learning independent in students will appearence in active attitude to follow learn activity. Learning independent is depend to create and accustom early. A learning competence and independent in students will reached if teacher can created learn condition to approriote. One of them is arrange module material. Module is a complete unit what consist on structure learn activity what will arrange for help they for reached a number of purpose what will formula according to special and clear.